2020
DOI: 10.1111/ger.12470
|View full text |Cite
|
Sign up to set email alerts
|

Primary diffuse large B‐cell lymphoma of the mandible: A case report

Abstract: IntroductionLymphomas are a heterogeneous group of malignant neoplasms of lymphocytes and their precursor cells. Lymphoma is seen 3.5% of all intraoral malignancies and is the second most common neoplasm after the squamous cell carcinoma in the head and neck region. Diffuse large B‐cell lymphomas (DLBCL), which is a subtype of non‐Hodgkin lymphoma, are seen mostly in the paraoral region.Case presentationAn 82‐year‐old woman was referred with a localised swelling of the mandibular buccal mucosa for 3 months. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Considering that 6-8 cycles of combined chemotherapy with R-CHOP-21 is the most widely used regimen for patients from 60 to 80 years of age, rituximab was added to the CHOP regimen for the patient in our case, though there is limited experience of the use of anti-CD20 medication during maintenance or consolidation for NHL initial presentation. The average time, reported in previous literature, to arrive at a definitive diagnosis for lymphoma which manifested as a toothache was approximately 5 months [ 5 , 15 , 16 ], while that of our case was about 1 month. With comprehensive inspection and prompt treatment, the patient's symptoms resolved, and no recurrence was seen in the following 5 years.…”
Section: Discussionmentioning
confidence: 54%
“…Considering that 6-8 cycles of combined chemotherapy with R-CHOP-21 is the most widely used regimen for patients from 60 to 80 years of age, rituximab was added to the CHOP regimen for the patient in our case, though there is limited experience of the use of anti-CD20 medication during maintenance or consolidation for NHL initial presentation. The average time, reported in previous literature, to arrive at a definitive diagnosis for lymphoma which manifested as a toothache was approximately 5 months [ 5 , 15 , 16 ], while that of our case was about 1 month. With comprehensive inspection and prompt treatment, the patient's symptoms resolved, and no recurrence was seen in the following 5 years.…”
Section: Discussionmentioning
confidence: 54%
“…Lymphomas are malignant neoplasms of lymphocytes and their precursor cells. Freeman et al reported 28% of extra-nodal sites of NHL in the head and neck area and 2% in the oral cavity [6]. Traditionally lymphoma is classified into Hodgkin's (HL) and non-Hodgkin's lymphoma (NHL) and NHL involves the extra-nodal site including the gastrointestinal tract, central nervous system, and skin as well as in the head and neck area involving waldeyer's ring, buccal mucosa, tongue, maxilla, and mandible [7].…”
Section: Discussionmentioning
confidence: 99%
“…The first line therapy of treatment of DLBCL is CHOP (cyclophosphamide, hydroxy doxorubicin, oncovin, and prednisolone). The early stage of DLBCL is managed by both combinations of chemotherapy and radiotherapy [6].…”
Section: Fig 5 A-image Shows Post-surgical With Good Healing Of Tissu...mentioning
confidence: 99%
“…According to a study by Barone S et al, the most commonly involved sites are in the soft tissues of oral cavity, with an incidence rate presenting as 38.4%, 19.2%, and 11.5% for buccal mucosa, tongue and gingiva [ 44 ]. As for the clinical appearance, lymphoma occurring in the gingiva, buccal mucosa, and palate usually manifests as ulceration (Table 2 ) [ 39 , 45 56 ], while that of FL has been discussed above, and masses or nodular lesions may be observed or palpated under the mucosa of the palate, buccal, and tongue [ 39 , 45 , 50 , 51 , 57 60 ]. Swelling of the lip, palate, gingiva, or buccal mucosa may serve as alternative oral signs of lymphoma [ 61 64 ].…”
Section: Discussionmentioning
confidence: 99%